2020
DOI: 10.1186/s12885-020-07389-w
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial determinants of quality of life in breast cancer survivors: a scoping review

Abstract: Background Breast cancer care today involves state-of-the-art biomedical treatment but can fail to address the broader psychosocial and quality-of-life (QoL) issues associated with the transition to breast cancer survivorship. This scoping review examines the evidence on the influence of psychosocial determinants on QoL in breast cancer survivors. Methods Scoping review methodology was used to: (1) identify the research question(s); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 105 publications
2
33
0
1
Order By: Relevance
“…This reflects the fact that positive psychological states can be shown in different aspects, and are positively correlated with each other [23]. Consistent with previous reports, it was found that confrontation, perceived social support, and resilience were positively associated with HRQoL, which indicated that a sound psychological state was beneficial to HRQoL improvement [8][9][10][11][12]. Although avoidance is a negative coping style, it was still helpful in protecting the BCSs' psychological defense system, which allowed more time for them to recover from their distress [24].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This reflects the fact that positive psychological states can be shown in different aspects, and are positively correlated with each other [23]. Consistent with previous reports, it was found that confrontation, perceived social support, and resilience were positively associated with HRQoL, which indicated that a sound psychological state was beneficial to HRQoL improvement [8][9][10][11][12]. Although avoidance is a negative coping style, it was still helpful in protecting the BCSs' psychological defense system, which allowed more time for them to recover from their distress [24].…”
Section: Discussionsupporting
confidence: 87%
“…With the increased survival rate, health professionals have paid more attention to the psychological rehabilitation of BCSs [4]. The variables most commonly focused on were social support, psychological symptoms, emotional functioning, coping styles, confidence and self-efficacy, and future perspective and appraisal [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature highlights the significant impact of social support related to health-related quality of life. 9,10 Health care providers need to consider whether there is sufficient support available to deal with the increased concerns faced by cancer survivors during this pandemic. In order to ensure that the health needs and quality of life of cancer patients is not negatively impacted, providers of psychosocial support may need to make strategic changes in the provision of access to health and support services.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to early diagnosis and more effective therapies, the long-term survival of some cancer patients increased over the years [ 11 ], e.g., breast cancer 5-year net survival in high income countries is now 85–90% [ 12 ]. Nevertheless, the disease still affects the independence in performing daily living activities, also due to treatment-related disabling complications (e.g., breast cancer-related lymphedema, axillary web syndrome) [ 11 ] and psychosocial distress [ 13 ]. To date, however, country-specific estimates of the morbidity burden of cancer in terms of YLD are lacking, despite the existence of an exhaustive cancer registry.…”
Section: Introductionmentioning
confidence: 99%